Economic Crime in Malaysia: An analysis into the changing role of the police - Nook, Yusoff Bin (1993)
Economic recession took effect in Malaysia in late 1984 and continued through 1985 and 1986. During this period, there was a sudden surge in economic crime. Its scale has Increased over recent years. When economic crime is on the increase, the costs to society are also increasing, not only in terms of money and property stolen by perpetrators, but also in terms of loss of confidence and respect by the public at large in our government. With the present rapid growth in business and commercial activities, economic crime has found a fertile ground. Economic crime is a 'growth industry'. Unless we study it, understand it, and develop tools to deal with it effectively, we may be witnessing only the beginning of a phenomenon that could undermine the social, economic and political stability of the country. Today's cost of economic crime in Malaysia is estimated to be more than $200 million a year. It victimises thousands of individuals. It undermines the very legitimacy of our institutions. With continued innovation in information and communications technologies, the dimensions of the problem expand; yet our legal and business systems cannot cope with what is happening today. In the opinion of the researcher, there can be little doubt that economic crime will continue to rob society as it has In the past. Despite its current scale, there has not been a study of economic crime In Malaysia. The reason is obvious; for a researcher to embark on a study in this particular area of criminal activity, there would need to be the accessibility to the highly sensitive data on such activities (while recognising that not all the crimes are detected). Many of the agencies charged with Investigation and prosecution of these non-traditional crimes, quite correctly, do not make their detailed findings public. Aggregated data, which are made available to the public, are often not sufficiently specific for research purposes. The secrecy of the Government agencies Is necessary in order for them to function effectively as law enforcement Instruments. Sutherland [1977, page 38] noted that explanations for crime could not be found in poverty alone; criminality is a much more complex phenomenon. For example, he noted that poverty Is no explanation for crimes of the rich and the professional segments of the society. It is noted by this researcher in his three years experience as the Head of Banking and Financial Investigations at the special unit of the Commercial Crime Department, Police Headquarters, Kuala Lumpur, that the problems In dealing with economic crimes could not be addressed in the same manner as In traditional crime. Studies were needed to explain and understand these crimes. From this knowledge base, there would be a better opportunity to formulate policy strategies to address the problems.This research, even though focussing in Malaysia, is meant to act as a springboard for future research within the researcher's organisation, the Royal Police Force of Malaysia, and also at least be useful for new Developing Countries which may have to encounter a similar economic crime phenomenon. The study also examines the major economic institutions in Malaysia such as cooperatives, insurance and stock-exchange and concludes that some of the main causes of economic crime are problems of management. They are: * poor quality and laxity of discipline and management; * financial and technical mismanagement in the operation of companies; * breaches of the law; * poor documentation and record keeping practices; * inadequate and ineffective control system. The findings of the research survey shows that the causes of economic crime in Malaysia are consistent with situational, opportunity and personal pressures. Economic crime in Malaysia is largely due to people who are in position of trust, who have abused their powers in a situation of poor accounting practices. Economic crime could possibly be prevented by improving the system of auditing, improving the management information system and improving the management environment